2005
DOI: 10.1097/01.ico.0000160975.81200.09
|View full text |Cite
|
Sign up to set email alerts
|

Femtosecond Laser-Assisted Intracorneal Keratoprosthesis Implantation

Abstract: Femtosecond laser corneal dissection provides an alternative to more challenging manual dissection methods for keratoprosthesis implantation. Use of the femtosecond laser microkeratome will further refine keratoprosthesis surgical technique and may allow rapid and easy execution of the surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…The manufacturer's recommended steps for Kpro preparation involve punching the donor with an 8.5-mm or greater diameter followed by a 3-mm central punch, but creating the inner 3-mm hole first, centering the outer ring on the Improving Boston keratoprosthesis procedure inner hole, has been hypothesized to improve centration (12). Sarayba et al (13) demonstrated an alternative to more challenging manual dissection methods for Alpha-Cor-like Kpro implantation and centration with femtosecond laser: the surgical technique was further refined and allowed for rapid and easy execution. Moshirfar et al (14) described a replicable technique for femtosecond laser-assisted preparation on an artificial chamber of donor tissue for Boston type 1 Kpro, to provide accurate double trephination for optimized alignment in the visual axis.…”
Section: An Active Keratoprosthesis Research Program Continues Inmentioning
confidence: 99%
“…The manufacturer's recommended steps for Kpro preparation involve punching the donor with an 8.5-mm or greater diameter followed by a 3-mm central punch, but creating the inner 3-mm hole first, centering the outer ring on the Improving Boston keratoprosthesis procedure inner hole, has been hypothesized to improve centration (12). Sarayba et al (13) demonstrated an alternative to more challenging manual dissection methods for Alpha-Cor-like Kpro implantation and centration with femtosecond laser: the surgical technique was further refined and allowed for rapid and easy execution. Moshirfar et al (14) described a replicable technique for femtosecond laser-assisted preparation on an artificial chamber of donor tissue for Boston type 1 Kpro, to provide accurate double trephination for optimized alignment in the visual axis.…”
Section: An Active Keratoprosthesis Research Program Continues Inmentioning
confidence: 99%
“…One study of eight corneoscleral rims created a 2.5 mm posterior corneal hole and 7.2 mm diameter stromal pocket, using femtosecond laser, with insertion of an intracorneal Alpha Cor-like Kpro into the stromal pocket 6. In a nonrandomized prospective study, femtosecond top hat PKP versus manual top hat PKP had better visual outcomes, less astigmatism, higher endothelial counts, and a trend toward less rejection 7.…”
Section: Introductionmentioning
confidence: 99%